Monstrousity and the (re)creation of Argentine history: an analysis of La asombrosa excursión de Zamba - Gastaldi, Sebastián Matías (2024)
Fil: Gastaldi, Sebastián Matías. Unieversidad Nacional de Córdoba. Facultad de Ciencias Sociales; Argentina.